NOTES ON MALESIAN FUNGI-II* On the genera Auricularia, Hirneola, and Laschia - DONK, M. A. (Research Center for Biology, 1952)
1. After discussing the outer characters of the three genera Auricularia Bull,ex Merat, Hirneola Fr. (1848), and Laschia Fr., now often combined into a single genus, the author concludes that there is every reason to follow Bresadola and to keep Auricularia and Hirneola apart as distinct genera, and to enter Laschia into Hirneola. 2. It is pointed out that in Hirneola the hymenophore is not invariably inferior. 3. The author once more discusses the desirability of conserving the name Hirneola Fr. 1848. He withdraws his previous proposal for conservation of Auricularia Bull, ex Brongn. 1824. 4. The new combination Hirneola nigricans (Sw. ex Fr.) Donk is proposed. 5. It is possible that the correct name for the Judas ear is Hirneola auricula(L. ex Mexat) H. Karst.